Comparison of Water Immersion Versus Air Insufflation Colonoscopy Under Various Bowel Preparation Conditions - Niu, Sijia; Yang, Youlin; Shang, Guoyin; Chen, Yingying; Ma, Zhibin; Wu, Feng; Zhang, Huichao (Turkish Journal of Gastroenterology, 2021)
Background: To investigate the differences between water immersion (WI) and air insufflation (AI) for colonoscopy under various bowel preparation conditions. Methods: In this study, 526 outpatients were randomly assigned to two groups, namely a WI group (n = 263) and an AI group (n = 263). During the procedure, the quality of bowel preparation, abdominal pain score, cecal intubation rate (CIR), adenoma detection rate (ADR), the intubation times, and other indicators were recorded. After reaching the cecum, each group of patients was subdivided into one of four grades (excellent, good, fair, and poor) according to the quality of bowel preparation. Results: Under various bowel preparation conditions, the pain scores of the AI group were higher than those of the WI group (P < .05), but there was no significant difference between the two groups in CIR (P > .05). For the WI group compared with the AI group, the cecal intubation time (CIT) was prolonged under good bowel preparation (P = .045) and fair bowel preparation (P < .001). No significant differences were observed between the two groups on ADR in all patients (P = .476). Conclusion: Compared with AI colonoscopy, WI colonoscopy can decrease colonoscopy-related pain in patients for unsedated colonoscopy under various bowel preparation conditions, but there is no significant difference in CIR. WI colonoscopy requires longer CIT in patients with good and fair bowel preparation conditions. WI colonoscopy does not significantly increase ADR.